Phylogeography of Mabuya maculilabris (Reptilia) from São Tomé Island (Gulf of Guinea) inferred from mtDNA sequences - Jesus, José (2020)
The pattern of genetic variation of the lizard Mabuya maculilabris from São Tomé Island (Gulf of Guinea) was investigated using a combination of three mitochondrial DNA gene fragments. Forty-eight haplotypes were recovered among 66 individuals covering the whole island. The genealogy inferred from the most parsimonious network of haplotypes allows us to detect two main and long branches departing from the putative group of oldest haplotypes. The tips of these branches exhibit star-like phylogenies, which may indicate of recently expanded populations, most probably from a small number of founders. A nested clade analysis suggests a complex pattern of past events that gave rise to the extant geographical pattern found in the haplotype distribution: past and allopatric fragmentation, range expansion, restricted gene Xow and long-distance dispersal. These results are consistent with the complex geological history of the island where important volcanic activity with extensive lava Xows has occurred during several periods. Mismatch-distribution analysis and AMOVA also support these conclusions. Substantial genetic structuring among these lizards was detected as well as high levels of diVerentiation between the southern edge populations (particularly those from the Rolas Islet) and the remaining ones. However, variation is low relative to the geological age of the island. Our results indicate that patterns of variation observed in reptiles in other oceanic islands are not indicative of those observed in the islands of the Gulf of Guinea.